Biomechanical analysis of motional actions of athletes engaged in short track speed skating during the turning phase - Volodymyr Ashanin; Nataliia Dolgopolova; Mariia Dolgopolova; Ludmila Filenko; Vladlena Pasko (Kharkiv State Academy of Physical Culture, 2021)
Purpose: development of a model for theoretical analysis and assessment of optimal biomechanical characteristics in the turn phase of short track skating athletes using existing biomechanical ergogenic devices and information technologies in the training process. Material and methods: theoretical analysis of scientific and methodological literature, analysis of web resources, pedagogical observation, video filming, biomechanical analysis of motor actions. The test group consisted of 10 young short trackers 9-12 years old and 5 short trackers aged 18-24 years, who practice short track speed at least three times a week (from 1 year old, for young athletes) and regular trainings five times a week (about 6-10 years, for adult athletes). Results: the paper theoretically analyzes the characteristics of the technique of passing the turning phase of short track speed skating athletes by means of biomechanical analysis. By calculation, the theoretical dependences of the indicators of the passage of the turning phase were determined: speed, the angle of inclination of the athlete's body in the turn, the position of the general center of mass of the body and their relationship. The main mistakes of the technique of motor actions fulfillment of beginner athletes in the turning phase are highlighted. Conclusions: these theoretical studies confirm the feasibility of using special devices to create conditions that simulate the real situation of an athlete passing a short track turn on one skate, and the coach can control the correct execution of movements by novice athletes from the point of view of biomechanics. The use of special elastic bands as ergogenic means for improving the motor actions of short track speed skating athletes is grounded. The ways of improving the biomechanical indicators, which the athlete is able to implement in practice, are indicated.